2013
DOI: 10.1007/s10965-013-0164-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the polymerization of 1-octene promoted by vanadium and titanium complexes supported by phenoxyimine and salen type ligands

Abstract: Polymerizations of 1-octene were carried out in the presence of vanadium and titanium complexes bearing salentype or phenoxyimine ligands activated with various cocatalysts. Vanadium complexes turned out active only in conjunction with MAO, whereas the titanium ones were active in combination with Al(i-Bu) 3 /Ph 3 CB(C 6 F 5 ) 4 . The activity of all catalysts was moderate or low and it was dependent on the ligand type: bis(phenoxyimine) complexes were more active than the salen ones. Both vanadium and titaniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Particularly, the IR spectra of 2a – 2g show the absence of O─H stretching bands in the range 3332–3453 cm −1 indicating the coordination of the phenoxy group to the vanadium metal center. Furthermore, the IR spectra of the these complexes show absorption bands at 1592–1619 cm −1 corresponding to the coordinated HC═N unit of the ligands ( 1a – 1g ) …”
Section: Resultsmentioning
confidence: 99%
“…Particularly, the IR spectra of 2a – 2g show the absence of O─H stretching bands in the range 3332–3453 cm −1 indicating the coordination of the phenoxy group to the vanadium metal center. Furthermore, the IR spectra of the these complexes show absorption bands at 1592–1619 cm −1 corresponding to the coordinated HC═N unit of the ligands ( 1a – 1g ) …”
Section: Resultsmentioning
confidence: 99%
“…3(a)). 43,44 The integration ratios of the three signals were 16 : 10 : 1.0, which corresponded to the molar ratios of vinylidene (CvCH 2 ), trisubstituted vinylene (-(C)CvCH-), and disubstituted vinylene (-CHvCH-) being 16 : 20 : 1.0. This assignment agreed with the integration values observed for allylic CvC-CH 2and CvC-CH 3 signals at 2.0-2.2 ppm and 1.6-1.8 ppm, respectively.…”
Section: α-Olefin Oligomerization Studiesmentioning
confidence: 98%
“…3(b)). 43,44 It has been previously reported that atactic PAO is better for lubricant applications because it exhibits a low pour point relative to the isotactic-or syndiotactic-rich analogs. 31…”
Section: α-Olefin Oligomerization Studiesmentioning
confidence: 99%
“…In a report by Białek et al , the well-known salen ligand (salen = N , N ′-bis(salicylidene)ethylenediamine) and its vanadium complex were investigated in 1-octene polymerization. 109 The V-salen catalyst produced poly(1-octene) in the presence of MAO and displayed atactic structures with a [mmmr] sequence (∼35%) at room temperature. Moreover, the activity was very poor (<3.0 kg mol cat −1 ) accompanied by a broad molecular weight distribution ( M w / M n = 5.3), clearly indicating the presence of multiple active sites.…”
Section: Catalytic Dimerization and Oligomerization Of 1-octenementioning
confidence: 99%